Differential Regulation of Allergic Airway Inflammation by Acetylcholine - Roberts, Luke B.; Berkachy, Rita; Wane, Madina; Patel, Dhiren F.; Schnoeller, Corinna; Lord, Graham M.; Gounaris, Kleoniki; Ryffel, Bernhard; Quesniaux, Valerie; Darby, Matthew; Horsnell, William G. C.; Selkirk, Murray E. (Frontiers in Immunology, 2022)
Acetylcholine (ACh) from neuronal and non-neuronal sources plays important roles in the regulation of immune responses and is associated with the development of several disease pathologies. We have previously demonstrated that group 2 innate lymphoid cell (ILC2)-derived ACh is required for optimal type 2 responses to parasitic infection, and therefore sought to determine whether this also plays a role in allergic inflammation. RoraCre+ChatLoxP mice (in which ILC2s cannot synthesize ACh) were exposed to an allergenic extract of the fungus Alternaria alternata, and immune responses in the airways and lung tissues analysed. Airway neutrophilia and expression of the neutrophil chemoattractants CXCL1 and CXCL2 were enhanced 24 hours after exposure, suggesting that ILC2-derived ACh plays a role in limiting excessive pulmonary neutrophilic inflammation. The effect of non-selective depletion of ACh was examined by intranasal administration of a stable parasite-secreted acetylcholinesterase. Depletion of airway ACh in this manner resulted in more profound enhancement of neutrophilia and chemokine expression, suggesting multiple cellular sources for release of ACh. In contrast, depletion of ACh inhibited Alternaria-induced activation of ILC2s, suppressing expression of IL-5, IL-13 and subsequent eosinophilia. Depletion of ACh resulted in a reduction of macrophages with an alternatively activated M2 phenotype, and an increase in M1 macrophage marker expression. These data suggest that ACh regulates allergic airway inflammation in several ways, enhancing ILC2-driven eosinophilia, but suppressing neutrophilia through reduced chemokine expression.